Authentication of Panax ginseng from different regions. Issue 88 (8th December 2017) - Yin, Juxin; Wang, Liwu; Huang, Yi; Mu, Ying; Lv, Shaowu
Abstract : The correlation of gene expressions of HMGR and DS with total ginsenoside content was significant. Abstract : Background : Panax ginseng is a type of traditional medicine. Fresh ginseng is one of the most important ingredients used in the medical industry. Fresh ginseng from different regions has different quality and significantly different prices; consequently, widespread adulteration occurs in the commercial market. However, little scientific guidance for determining the origin of fresh ginseng from different regions is available. We proposed a new strategy for identifying fresh ginseng from different regions. Methods : we investigated the content of ginsenoside, and the activity and gene expression of seven key enzymes involved in ginsenoside biosynthesis. HPLC was used to determine the content of ginsenosides. Gene expression was studied using qRT-PCR. HPLC, GC-MS, LC-MS, enzyme-linked immunosorbent assayand colorimetry were used to measure the activities of key enzymes. Results : the gene expression of the key enzymes 3-hydroxy-3-methylglutaryl CoA reductase (HMGR) and dammarenediol synthase (DS) was consistent with the saponin content of fresh ginseng from different regions. The correlation of gene expressions of HMGR and DS, and the content of the ginsenoside Re with total ginsenoside content, was significant. Conclusion : HMGR and DS gene expression and the content of the ginsenoside Re are important for the authentication of ginseng from different regions. Our research provides an important reference for further studies on the regulatory mechanism of the biosynthetic pathway of ginsenosides.